(untitled) (Research, Society and Development, 2021)
Objective: To analyze the initial responses of the Bahia’s parliament in confronting the COVID-19 pandemic. Methodology: Exploratory and descriptive study, carried out through documentary research, from access to public information available on the website of the Legislative Assembly of Bahia. Twenty minutes of virtual plenary sessions were investigated, as well as 374 legislative proposals referring to COVID-19. The period of analysis was from March to June 2020, which corresponds to the beginning of COVID-19 in Brazil and precedes the first peak of cases in Bahia. An analysis matrix was elaborated, based on the variables: date of entry, proposal, author, party / bench, measure, position taken, status of processing. Results: From the point of view of the decision-making process, it was not possible to change independently with the transposition from physical to virtual arena, in addition to adjustments of an organizational nature. Only 3 categories of proposals were approved: the declarations of public calamity; how they established guidelines/measures/management mechanisms; and as practical / fiscal, suggesting an effort to prepare the public machine to fight the pandemic. Among the sanctioned laws, it was found: broad role of the executive; quick processing time of matters; the predilection for social protection policies, with income transfer; effort in combating false news; reinforcement of the WHO recommendations. Finnish considerations: One of the effects of the virtual regime was the reduction of popular participation in parliament and the distance between political agents and their electorate. Some actions were recommended, such as the updating of public data, the strengthening of formal parliaments and the permanent monitoring of state legislatures.